2022
DOI: 10.7554/elife.76389
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid signaling mediates peripheral cone photoreceptor survival in a mouse model of retina degeneration

Abstract: Retinitis Pigmentosa (RP) is a progressive, debilitating visual disorder caused by mutations in a diverse set of genes. In both humans with RP and mouse models of RP, rod photoreceptor dysfunction leads to loss of night vision, and is followed by secondary cone photoreceptor dysfunction and degeneration, leading to loss of daylight color vision. A strategy to prevent secondary cone death could provide a general RP therapy to preserve daylight color vision regardless of the underlying mutation. In mouse models … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 79 publications
(107 reference statements)
1
11
0
Order By: Relevance
“…Compared to the P21 retina, P40 ARR3 staining was dramatically decreased in the central retina of both Rlbp1 −/− ; rd1 and Rlbp1 +/+ ; rd1 mice, suggesting severe cone degeneration and death from P21 to P40 ( Fig. 4 B ), as has been reported for the rd1 strain ( 36 ). Nonetheless, when the number of ARR3+ cells in P40 rd1 retinas was quantified, there were significantly more cones (ARR3+ cells) in the central retina of Rlbp1 −/− rd1 mice relative to the Rlbp1 +/+ rd1 mice ( Fig.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…Compared to the P21 retina, P40 ARR3 staining was dramatically decreased in the central retina of both Rlbp1 −/− ; rd1 and Rlbp1 +/+ ; rd1 mice, suggesting severe cone degeneration and death from P21 to P40 ( Fig. 4 B ), as has been reported for the rd1 strain ( 36 ). Nonetheless, when the number of ARR3+ cells in P40 rd1 retinas was quantified, there were significantly more cones (ARR3+ cells) in the central retina of Rlbp1 −/− rd1 mice relative to the Rlbp1 +/+ rd1 mice ( Fig.…”
Section: Resultssupporting
confidence: 73%
“…Our results may also help to explain a recent finding regarding a protective effect of retinoic acid (RA) on RP cone survival. We found that RA, produced by ALDH1A1 in peripheral Müller glia, protected peripheral cones in a RP mouse model ( 36 ). This enzyme might contribute to cone survival by changing the retinaldehyde to the acid form.…”
Section: Discussionmentioning
confidence: 93%
“…Considerable effort has been made to find ways to protect cones in animal models of retinal degeneration [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] and some identified modifiers of cone death are currently being evaluated in clinical trials 65 . However, no treatment for protecting cones in photoreceptor diseases such as macular degeneration or retinitis pigmentosa has yet received approval for use in humans.…”
Section: Compounds That Protect Human Conesmentioning
confidence: 99%
“…Retinitis pigmentosa, a group of monogenic retinal diseases, primarily affects rods 29,30 and cones degenerate as a secondary consequence of rod death 31 . The reasons behind cone degeneration in age-related macular degeneration and retinitis pigmentosa are extensively studied but are not fully understood, and several approaches are being developed to halt the degeneration process [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] . However, slowing down cone degeneration in patients has so far not been achieved.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the former case of Gnat1 –/– ; Cnga3 –/– knockouts, some alternative pathway for rod signaling via cone photoreceptors, locked in “light” state by Cnga3 disruption, seems to be retained ( Allen et al, 2010 ), providing a confounding mechanism for the observed photosensitivity. Similarly, in Rd1 mouse models it has been demonstrated that a small portion of cone photoreceptors in the peripheral retina survive into P90 ( Lin et al, 2009 ) and beyond ( Amamoto et al, 2022 ), and could explain residual photosensitivity in these animals. To address these potentially confounding issues, here we employed the Gnat1 –/– , Gnat2 cpfl3/cpfl3 mouse model, in which the genes encoding the α-subunit of both rod- and cone-transducin have been knocked out and mutated, respectively.…”
Section: Introductionmentioning
confidence: 96%